APLIKASI SISTEM PEMBELAJARAN INTERAKTIF PENGENALAN RANGKA TUBUH DAN PANCA INDERA MANUSIA - Lisdarti - (JURNAL AKADEMIKA)
Junior High School is an institution or a school, which now has evolved along with the times , with the teaching methods applied today may be out with the sophistication of modern technology already , with the creation of a multimedia -based interactive media the framework of the body and get to know the human senses which is expected to help ease the teaching staff ( teachers ) in teaching and learning , in the media there is some discussion of this interactive that is familiar with the framework of the body and the human senses . And there is a little extra on the evaluation of the framework of the body and the human senses , and there is some information about the institutive and authors . While the output of the media interaction is a display of the frame body and the human senses to be selected by the user . This interactive media applications built using Adobe Flash CS3 application as the main application . The expected outcome of this interactive media applications are getting better and smooth the learning method on SMP.